Myth, History and Archaeology : Essays and Reviews, 2000-2025 - Wiseman, T.P., (Classical Studies E-Books Online, Collection 2025., 2026)
A bronze mirror of the fourth century BC shows a she-wolf suckling infant twins. You may think that's a familiar story, but who are the other figures in the scene, and why is there a lion so prominent in the foreground? The image typifies the problems involved in studying the history and evolution of mythic stories in the ancient world. This collection of studies, prompted by a famous archaeologist's quasi-historical reinterpretation of the Romulus legend, seeks to achieve greater clarity by avoiding abstract concepts like 'oral tradition' or 'cultural memory' and paying close attention to what the primary sources presuppose.